Еволюція стилю байки (на матеріалі української, російської та німецької віршованої байки) - Піхтовнікова, Л.С. (Харківський національний університет імені В.Н. Каразіна, 2006)
В статье описана эволюция стиля украинской и русской басни в течение трех веков. Установлены стилевые архетипы басен, показаны единые законы развития метафоры и образа-символа басни, а также их взаимное соответствие. Для сравнения и подтверждения универсальных законов эволюции представлен путь развития стиля немецкой басни, установленный в докторской диссертации автора. The style of Ukrainian and Russian fable in diachrony during three centuries is described in the paper. The style archetypes of fables are determined; similar development principles of metaphor and symbol af a fable and their mutual adequacy are displayed. The style development of German fable determined by the author in Doctorate thesis is presented in order to compare and prove the universal principles of fable development.
Keywords: стиль байки; байка; образ-символ байки